2011
DOI: 10.1021/ja2025189
|View full text |Cite
|
Sign up to set email alerts
|

Size-Dependent Reactivity in Hydrosilylation of Silicon Nanocrystals

Abstract: We present an investigation into the influence of nanocrystal size on the reactivity of silicon nanocrystals (Si-NCs) in near-UV photochemical hydrosilylation. The size-dependent reactivity of Si-NCs with photoluminescence (PL) in the visible and near-infrared regions was evaluated using PL and Fourier-transform infrared (FTIR) spectroscopy, and small-angle X-ray scattering (SAXS). Under near-UV excitation, Si-NCs with PL in the visible spectral region react faster than Si-NCs with near-IR PL, allowing partial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
88
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(101 citation statements)
references
References 65 publications
7
88
0
Order By: Relevance
“…[ 24,32 ] Recent synthetic advances have resulted in well-defi ned silicon nanocrystals (SiNCs) that have bettered the community's understanding of their properties and reactivity. [33][34][35][36] Modern SiNCs exhibit many, if not all of the favorable properties of traditional QDs with the added benefi t of being non-toxic. [37][38][39][40][41][42] Their surface chemistry differs substantially from that of other QDs and is routinely tailored via various hydrosilylation approaches that afford robust covalent Si-C bonds.…”
Section: Introductionmentioning
confidence: 99%
“…[ 24,32 ] Recent synthetic advances have resulted in well-defi ned silicon nanocrystals (SiNCs) that have bettered the community's understanding of their properties and reactivity. [33][34][35][36] Modern SiNCs exhibit many, if not all of the favorable properties of traditional QDs with the added benefi t of being non-toxic. [37][38][39][40][41][42] Their surface chemistry differs substantially from that of other QDs and is routinely tailored via various hydrosilylation approaches that afford robust covalent Si-C bonds.…”
Section: Introductionmentioning
confidence: 99%
“…Veinot et al showed a strong size dependence of hydrosilylation efficiency for silicon nanoparticles. Particles with 5 to 7 nm in diameter required significant longer reaction times than the particles with 2 to 3 nm in diameter and still showed worse functionalization efficiencies [12]. These effects are attributed to changes in reaction chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…There are issues with the attachment of such groups to a silicon surface, since the typical hydrosilylation method for SiNPs functionalization does not give desirable high surface coverage. 23 This is due to the ability of such surface agents, once attached to quench the reactive species. 24 However, an alternative method is the reaction of a suitable nucleophile with chloride terminated SiNPs.…”
mentioning
confidence: 99%